THE CREATIVE MARKETING STRATEGY IN DEVELOPING PANDAN WOVEN PRODUCTS IN THE MARKET AT MSMES “JAXEE” - Ismaya, Sakti Brata; Indrajaya, Titus; Widyasari, Lala; Tukiyat, Tukiyat; Supriyani, Mei (Yayasan Education and Social Center, 2024)
The economic crisis caused by the COVID-19 pandemic at the beginning of 2020 has significantly impacted the micro, small and medium enterprise (MSME) sector in this country. In this context, this research examines the strategic efforts UMKM